Measurement of Tannic Substances in Forest Species - Medeiros, Jordania Xavier de; Calegari, Leandro; Silva, Girlanio [UNESP]; Oliveira, Elisabeth; Pimenta, Alexandre (Univ Federal Rural Rio De Janeiro, Inst Florestas, 2018)
This study aimed to quantify the tannic content of the barks and fruit of angico-vermelho, jurema-preta and acacia-negra using skin powder as detanizador agent. Materials from these species were ground and classified, with 12.5g of air dried particles subjected to extraction using a steam jacket type extractor to obtain 1000 ml of solution, using a completely randomized analytic design. The solution was evaluated using four treatments: angico bark; jurema bark; acacia bark and angico fruit. Three replicates per treatment were realized and subrepetitions were analyzed in triplicate. The results were interpreted by comparison of means with Tukey test at 5% significance. Best results in terms of total solids content, were observed in acacia bark (67.2%), differing statistically for angico bark (63.5%). The soluble solids content, in turn, was superior to angico bark (60.3%), differing statistically from acacia bark (49.8%). No statistically significant differences for tannin content were observed between acacia and angico barks, which presented values of 28.4 and 26.8%, respectively.
Keywords: skin powder; extractive; vegetable tannins